Spaceborne measurement of Greenland ice sheet changes: the ESA Greenland CCI project - Forsberg, René; Sørensen, Louise Sandberg; Meister, Rakia; Simonsen, Sebastian Bjerregaard; Dall, Jørgen; Kusk, Anders; Nagler, Thomas; Hetzenegger, Marcus; Evensberget, Dag; Hauglund, Kenneth; Khvorostovsky, Kirill; Shepherd, Andy; et al. (2016)
The ESA “Greenland_ice_sheet_cci” project is currently making past and present space measurements of Greenland ice sheet changes available for use by scientists, stakeholders and the general public. The data are part of a large set of ECV’s (Essential Climate Variables) made available by the ESA Climate Initiative, as a contribution to the global Climate Observing System. The ECV data produced for the Greenlandice sheet include detailed grids of elevation changes and ice flow velocities, as well as line data of grounding lines and calving front locations for major outlet glaciers. The “ice_sheets_cci” goal is to generate a consistent, validated, long-term and timely set of ECV’s, a.o. to improve the impact of satellite data on climate research and coupled ice sheet/climate models. Special focus is on use of data from ESA missions such as ERS, Envisat and the new Sentinel missions, but in the 2nd phase of the project, just initiated, mass balance data from the GRACE mission will also be included. In the presentation the current CCI results are highlighted, including Greenland-wide elevation change results across 23 years of radar altimetrry from ERS, Envisat and CryoSat, ice velocities for the coastal regions and major outlet glaciers, new Greenland-wide ice velocities from the ESA Sentinel-1 mission, and 14 years of mass changes from GRACE. The ECV data confirm a consistent overall picture of accelerating mass loss of the Greenlandice sheet, a mass loss which has more the doubled in the last decade. Current rates of changes well above 250 GT/year, corresponding to 0.7 mm/year global sea level rise, and originating especially from mass loss associated with major outlet glacier systems. In the future it is proposed to add additional ECV parameters to the products, including a.o. high-resolution mass change products from GRACE/CryoSat/S-3, and ocean sea level rise regional “finger print” data from the associated closure of the overall global sea level budget, in cooperation with Glaciers, Antarctica and Sea Level ...